2020
DOI: 10.7150/jca.47106
|View full text |Cite
|
Sign up to set email alerts
|

IL36 indicating good prognosis in human Hepatocellular Carcinoma

Abstract: Background and Aim: Hepatocellular carcinoma (HCC) is the leading cause of cancer death in men before the age of 60 years in China. Interleukin (IL)36 played important roles in antitumor immune responses, but its role in HCC is still unknown. We aimed to explore the correlation between IL36 and prognosis of HCC patients. Methods: The expression of IL36 was measured by Immunohistochemistry (IHC), serum Enzyme-linked Immunosorbent Assay (ELISA) and flow cytometry (FCM). Chi-square test was performed to analyze t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Our speculation is supported by others, indicating that IL-36 plays a critical role in tumor treatment and prognosis. 29 Furthermore, our data suggest that IL-36α may be a potential therapeutic target in the management of HCC, which is in line with the findings in colorectal cancer during the early stages of the disease. 30 Therefore, we believe that IL-36α is a novel prognostic marker for HCC.…”
Section: Discussionsupporting
confidence: 88%
“…Our speculation is supported by others, indicating that IL-36 plays a critical role in tumor treatment and prognosis. 29 Furthermore, our data suggest that IL-36α may be a potential therapeutic target in the management of HCC, which is in line with the findings in colorectal cancer during the early stages of the disease. 30 Therefore, we believe that IL-36α is a novel prognostic marker for HCC.…”
Section: Discussionsupporting
confidence: 88%
“…( Sarin et al, 2020 ) A study results showed that IL-36 was significantly expressed in HCC tumor tissues compared with adjacent peritumoral tissues, and its expression level was closely associated with clinical parameters, such as metastasis, alpha fetoprotein, HBV infection, and cirrhosis, but did not change with age and gender. ( Hu et al, 2020 ) The expression level of IL-36 has also been confirmed to be associated with the prognosis of liver cancer. Specifically, if the expression level of IL-36 was higher, the patients would have a better prognosis of liver cancer and a longer survival time.…”
Section: Introductionmentioning
confidence: 97%
“…These suggested that IL-36 may be a biomarker for HCC. ( Hu et al, 2020 ) Besides, although colorectal cancer (CRC) was the third most common cancer in the world, it was relatively common in Western societies ( Marley and Nan, 2016 ), and the incidence has also increased in China ( Maida et al, 2017 ) IL-36 could be produced at high levels in the colon, which was beneficial to the survival of CRC patients. ( Wang et al, 2014 ) In other words, high IL-36α in CRC patients had higher survival than low IL-36α patients.…”
Section: Introductionmentioning
confidence: 99%
“…In non-cancerous liver tissues, there is a constitutive level of intrahepatic IL-36; however, the expression of intrahepatic IL-36 is significantly suppressed in HCC tissues (23). Notably, HCC patients with higher intrahepatic IL-36 expression exhibit better survival outcomes, along with lower recurrence rates, compared to HCC patients with lower intrahepatic IL-36 expression (23).…”
Section: Il-36 In Hccmentioning
confidence: 99%